Microwave-Assisted Synthesis of (±)-Mandelic Acid-d5, Optical Resolution, and Absolute Configuration Determination. (6th September 2012) - Bruno, Claudio; Lentini, Giovanni; Lovece, Angelo; Cavalluzzi, Maria Maddalena; Carocci, Alessia; Catalano, Alessia; Franchini, Carlo
Abstract : An efficient microwave-assisted synthesis of ( ± ) -mandelic acid-d 5 was developed. The racemic mixture was resolved by diastereomeric salt formation using 1-phenylethylamine enantiomers as resolving agents. At each step, the resolution process was checked by determining mandelic acid-d 5 enantiomer ee values directly on fractional crystallized diastereomeric salts by chiral capillary electrophoresis analysis. Highly enriched (−)- and (+)-mandelic acid-d 5 (95% and 90% ee, resp.) were obtained and their absolute configurations— R and S, respectively—were determined by correlation of the (−)-mandelic acid-d 5 circular dichroism spectrum to the ( R )-mandelic acid one.